Effectiveness of Anadara granosa shell-Stichopus hermanni granules at accelerating woven bone formation fourteen days after tooth extraction - Rima Parwati Sari; Hansen Kurniawan (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Post-extraction complications can cause alveolar bone resorption. Hydroxyapatite-tricalcium phosphate (HA-TCP) is one potential bone graft material that can be synthesized from Anadara granosa shell. Another biomarine, Stichopus hermanni, contains hyaluronic acid which can accelerate bone formation on the fourteenth day. Purpose: This study aims to prove the effectiveness of Anadara granosa shell-Stichopus hermanni granules in weaving bone formation fourteen days after tooth extraction. Methods: Twenty-five male Wistar rats were divided into five groups. Their lower left incisor was extracted with gelatin being administered to the control group (C) and granule scaffold derived from Anadara granosa (AG) shell and Anadara granosa shell-Stichopus hermanni at concentrations of 0.4%-0.8%-1.6% (AGSH1-AGSH2-AGSH3) to the treatment group. This study developed a HA-TCP synthesized from Anadara granosa combined with whole Stichopus hermanni to create granule scaffolds by means of a freeze-dried method. The jaw was removed on the fourteenth day post-tooth extraction. Observation of HPA involved the use of an Image Raster®. The resulting data was subjected to analysis by ANOVA and tukey-HSD tests (p<0.05). Results: Data showed the mean of C=0.157±0.078; AG=1.139±0.371; AGSH1=1.595±0.291; AGSH2=1.740±0.308; and AGSH3=1.638±0.286. Statistical analyses showed significant differences in the woven bone area (mm2) between C and the treatment groups AG;AGSH1;AGSH2; AGSH3; and between AG and the AGSH2 groups. Conclusions: Scaffold granules from Anadara granosa shells and Stichopus hermanni effectively accelerate the bone formation process with the most effective being Stichopus hermanni at a concentration of 0.8%.